Oral rehabilitation with removable dental prosthesis in a six-year-old patient with hypohidrotic ectodermal dysplasia - Mariana Dalledone (RSBO Revista Sul-Brasileira de Odontologia, 2017)
Introduction: Ectodermal dysplasia is an abnormality of the ectoderm and its derivatives, phenotypically expressed in males and genetically inherited from mothers. Objective: To report the efficacy of the prosthetics treatment of severe ectodermal dysplasia in a 6-year-old boy with hypohidrotic ectodermal dysplasia (HED). Case report: The boy had difficulty in speaking and eating and the condition also affected his self-esteem. Prosthetic treatments included the construction of acrylic custom trays, determination of the vertical dimension of occlusion (VDO), construction of upper and lower dentures, and palatal expansion procedure. Conclusion: Significant improvements in the patient’s stomatognathic function and self-esteem were evident.